Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1103/physrevb.97.024304
|View full text |Cite
|
Sign up to set email alerts
|

Trapped-mode-induced Fano resonance and acoustical transparency in a one-dimensional solid-fluid phononic crystal

Abstract: We investigate theoretically and numerically the possibility of existence of Fano and acoustic-induced transparency (AIT) resonances in a simple though realistic one-dimensional acoustic structure made of solid-fluid layers inserted between two fluids. These resonances are obtained by combining appropriately the zeros of transmission (antiresonance) induced by the solid layers and the local resonances induced by the solid or combined solid-fluid layers with surface free boundary conditions. In particular, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 69 publications
(133 reference statements)
0
27
0
Order By: Relevance
“…Sound waves with frequency and direction corresponding to the cut do not propagate though a given layered structure. The effect of zero acoustic transparency through a solid plate surrounded by a fluid was recently predicted by Quotane et al 21 . This effect is due to a narrow Fano resonance caused by interference between a discrete trapped mode of a solid plate and a continuum of acoustic modes of a fluid.…”
Section: Resultsmentioning
confidence: 75%
“…Sound waves with frequency and direction corresponding to the cut do not propagate though a given layered structure. The effect of zero acoustic transparency through a solid plate surrounded by a fluid was recently predicted by Quotane et al 21 . This effect is due to a narrow Fano resonance caused by interference between a discrete trapped mode of a solid plate and a continuum of acoustic modes of a fluid.…”
Section: Resultsmentioning
confidence: 75%
“…Recent studies have demonstrated that the analog of EIT can be also realized in classical systems due to similar interference effects. Different systems have been proposed for this purpose such as: photonic crystal waveguides coupled to cavities [7][8][9], coupled-microresonator systems [10,11], nonlinear materials [12,13], plasmonic nanostructures and metamaterials [14,15], acoustic waveguides [16][17][18], multilayers [19] and photonic circuits [20,21]. In addition to the EIT resonances, the electromagnetically induced reflection (EIR) refers to the formation of a reflection window inside a transparency band of an atomic system.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial metamaterials, which own advantaged electromagnetic (EM) manipulating capability in dual negative refractive index modification [1,2], radar crosssection (RCS) reduction [3,4], frequency selectivity [5][6][7][8] and antenna properties improvement [9][10], have intrigued great interests for stealth domain [11,12], super-resolution imaging [13][14][15], energy harvesting [16][17][18][19] , beam scanning [20,21], and even acoustical [22][23][24], terahertz [25], optical [26][27][28] applications. EM manipulation means the efficient energy transfer or property transformation of absorbent metamaterials (AMs).…”
Section: Introductionmentioning
confidence: 99%